ADAPTATION OF MUSLIM FAMILY ACTIVITY IN OCCUPYING MINIMALIST CONTEMPORARY ARCHITECTURAL HOUSING DESIGN - Aulia, Dwira Nirfalini; Syafikri, Abdul Rahman (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2020)
The Muslim family's important criteria that inhabited their house are the needs of his family's privacy, creating an Islamic behavior (modesty) and entertaining guests (hospitality) who came to visit. The perception of these needs included the development of a minimalist contemporary architecture that is now widely grown. Contemporary minimalism is one type of architecture emerged in Indonesia, especially in Medan. The type is simple and small dimensions characterize minimalism. Does every Muslim family in the area of Medan (sample) is easily adaptable to the needs that exist in minimalist contemporary architecture include the need for privacy, modesty, and hospitality?. Therefore, the research purpose is to discover a Muslim family adaptation to the needs of space and performance. The method used was a qualitative method of mapping the behavior by place-centered mapping. Results from this study are the adaptation of living in the house to appropriate their needs and recommending improvements in the design of houses.